(untitled) (Advancements in Homeopathic Research, 2022)
Background: ‘Urolithiasis’ is a common disease in day to day clinical practice and represents with one of the most painful medical conditions. People suffering from recurrent complains of urolithiasis, needs careful examination for underlying metabolic disorders. It usually consist of crystalline deposits that accumulate primarily in kidney however, they can develop anywhere along urinary tract, which consists of these parts: kidneys, ureters, bladder, urethra. In homoeopathy there are hundreds of medicines for urolithiasis assuming various approaches. However, the constitutional approach is most suitable way to find out similimum but at times patients are not in condition of giving case taking because of acute pain, hence snapshort prescription is needed at those time to give relief to the patient. Location of stone in different parts of renal tract have important clue for selection of curative medicines. This article represents 2 cases of urolithiasis and represents classical example of prescription based on location, when other symptoms also agree. Result & conclusion: Oraganopathic prescriptions are made based on the Paracelsus principle that the given drugs affect given organs (parts) by self elective preference. This article emphasise on importance of organopathic approach as acute prescription with beneficial results along with documented evidence.